Ideologías enfrentadas: Job y el debate entre las sabidurías en el Israel posexílico = Conflicting ideologies : Job and the debate between the Wisdoms in Post-exilic Israel - Fonseca Ariza, Abiud (Revista de interpretação bíblica latino-americana, 2023)
The book of Job exposes an ideological debate between traditional wisdom and the new wisdom that was installed in Judea, at the end of the Persian period and the beginning of the Hellenic period. Ideology in the ancient world had religion as its substrate, which crossed all aspects of social life. The discussion involved a controversy between two divergent worldviews, both configured from their own imaginations of divinity, the human being, and the relationship between them; specifically in how justice is operated in this relationship. This ideological confrontation is registered in the extensive poetic section of the book, in the dialogues between Job and his interlocutors, and in the monologues. The proposals of the new wisdom found a positive response in the reading community, due to its conception of justice that went beyond the logic of retribution typical of priestly doctrine. Job’s poetry exposes more ideological tension than resolution.